Mathematical Modelling for Peristaltic Flow of Sutterby Fluid Through Tube under the Effect of Endoscope - Ammar, Neeran; Ali, Hayat A. (Iraqi Journal of Science, 2023)
In this work, the mathematical modelling of peristaltic transport for incompressible Sutterby fluid through the cavity between coaxial tubes where the inner tube is fixed and the outer tube has sinusoidal rhythmic fluctuations along the channel’s walls is presented. Under the assumption of long wavelength and the low Reynolds number, the governing equations (motion, temperature, and concentration) are illustrated in cylindrical coordinates. The analytical solution for the temperature and concentration of the fluid flow is obtained using Mathematica 11.3, whereas the perturbation technique is employed to find the closed form of the velocity profile. The variation of the axial velocity, stream function, temperature, concentration, and heat transfer are graphically discussed under the impact of interesting involved parameters.